Chemical composition, antimicrobial activity and synergistic effects with conventional antibiotics under clinical isolates by essential oil of Hymenaea rubriflora Ducke (FABACEAE). Issue 22 (18th November 2021) - da Silva, Graziela Claudia; de Veras, Bruno Oliveira; de Assis, Caio Rodrigo Dias; Navarro, Daniela Maria do Amaral Ferraz; Diniz, Dyana Leal Veras; Brayner dos Santos, Fábio André; de Aguiar, Júlio César Ribeiro de Oliveira Farias; da Silva, Márcia Vanusa; dos Santos Correia, Maria Tereza
Abstract: This work aimed to investigate the chemical composition, antimicrobial activity, synergistic effect, and structure changes of the essential oil of Hymenaea rubriflora (EOHr). Forty-five constituents were identified in the essential oil, corresponding to 94.43% of the compounds present, being the main components E-Caryophyllene (36.72 ± 1.05%), Germacrene D (16.13 ± 0.31%), α-Humulene (6.06 ± 0.16%), β-elemene (5.61 ± 0.14%) and δ-Cadinene (3.76 ± 0.07%). Antimicrobial activity was evaluated, presenting antibacterial and antifungal activity with MIC ranging from 0.62 to 40 μL/mL. The essential oil had a synergistic effect when combined with gentamicin and fluconazole. Structural changes were also evaluated and it was possible to observe that EOHr action was related to changes in membrane permeability. The findings obtained here suggest that the use of the essential oil of H. rubriflora in the treatment of infectious diseases presents a potential for the future development of pharmaceutical products. Graphical Abstract: